The Evolution of Lateral Lumbar Interbody Fusion: A Journey from Past to Present - Anthony Xi Jie Wong; Derek Haowen Tang; Arun-Kumar Kaliya-Perumal; Jacob Yoong-Leong Oh (Medicina, 2024)
Lumbar interbody fusion procedures have seen a significant evolution over the years, with various approaches being developed to address spinal pathologies and instability, including posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF), anterior lumbar interbody fusion (ALIF), and lateral lumbar interbody fusion (LLIF). LLIF, a pivotal technique in the field, initially emerged as extreme/direct lateral interbody fusion (XLIF/DLIF) before the development of oblique lumbar interbody fusion (OLIF). To ensure comprehensive circumferential stability, LLIF procedures are often combined with posterior stabilization (PS) using pedicle screws. However, achieving this required repositioning of the patient during the surgical procedure. The advent of single-position surgery (SPS) has revolutionized the procedure by eliminating the need for patient repositioning. With SPS, LLIF along with PS can be performed either in the lateral or prone position, resulting in significantly reduced operative time. Ongoing research endeavors are dedicated to further enhancing LLIF procedures making them even safer and easier. Notably, the integration of robotic technology into SPS has emerged as a game-changer, simplifying surgical processes and positioning itself as a vital asset for the future of spinal fusion surgery. This literature review aims to provide a succinct summary of the evolutionary trajectory of lumbar interbody fusion techniques, with a specific emphasis on its recent advancements.